Pengaruh Transaksi Pihak Berelasi Terhadap Performa Perusahaan Sektor Basic Materials di Indonesia - Pranita, Widya; Yaputri, Leticia; Farhana, Siti; Daniel, Daniel (Universitas Swadaya Gunung Jati, 2023)
AbstractThis study was conducted to determine the effect of related party transactions on company performance measured by return on assets (ROA) and Tobin's Q (TQ). Seeing that there are shortcomings in previous research, this study specifies related party transactions (RPT) into four types of transactions, namely sales, purchases, accounts receivable, and payables, and focuses the scope of research using only the basic materials sector. The sample consisted of 30 companies in the basic materials sector listed on the Indonesia Stock Exchange in 2015-2020, with a total of 180 observations. This study was carried out with two regression models, and several sensitivity tests to see differences in results with the main model. As a result, related party transactions do not have a significant effect on TQ, but there is a negative effect between sales transactions on ROA. The limitation of this study is the assumption that stock prices strongly react to the company's financial performance and do not carry out an analysis as a whole group or do not differentiate transactions made by subsidiaries or parent companies. This research is expected to provide new understanding to companies, investors, regulators, and academics regarding the effect of related party transactions on company performance.Keywords: Basic material sector; Performance; Related party transactions; ROA; Tobin’s Q Religiosity. AbstrakPenelitian ini dilakukan untuk mengetahui pengaruh transaksi pihak berelasi terhadap performa perusahaan yang diukur menggunakan return on aseet (ROA) dan Tobin’s Q (TQ). Melihat bahwa adanya kekurangan dalam penelitian sebelumnya, maka penelitian ini menspesifikasi transaksi pihak berelasi (RPT) menjadi empat jenis transaksi yaitu penjualan, pembelian, piutang, dan utang serta memfokuskan lingkup penelitian dengan hanya menggunakan sektor basic materials. Sampel yang digunakan pada penelitian ini, terdiri atas 30 perusahaan yang termasuk pada sektor basic materials dan terdaftar pada Bursa Efek Indonesia pada tahun 2015-2020, sehingga terdapat 180 observasi. Penelitian ini dijalankan dengan dua model regresi yang berbeda, serta melaksanakan beberapa uji sensitivitas untuk melihat perbedaan hasil dengan model utama. Sebagai hasil penelitian, ditemukan bahwa transaksi pihak berelasi tidak memiliki pengaruh yang signifikan terhadap TQ, namun terdapat pengaruh yang negatif antara transaksi penjualan terhadap ROA. Penelitian ini diharapkan mampu memberikan pemahaman baru kepada perusahaan, investor, regulator dan akademisi mengenai pengaruh transaksi pihak berelasi terhadap performa perusahaan.Kata Kunci: Performa perusahaan; ROA; Sektor bahan baku; Tobin’s Q; Transaksi pihak berelasi.